Pelatihan pembuatan keripik pakis dalam rangka meningkatkan produk unggulan pangan desa Setalik - Adi Pura; Tasya Safitri; Leni Leni; Sri Yuliani; Maria Felixia Randong; Mega Fitri; Pegi Aryasari (Universitas Pendidikan Indonesia (UPI), 2022)
Setalik Village is one of the villages located in Sejangkung District, Sambas Regency, West Kalimantan. Most of the agricultural products in Setalik Village are rice and rubber, while superior products are still not available. The purpose of this training is to increase the knowledge and ability of the village to make processed food products that can be superior. The approach taken in this activity consists of four stages of activity, namely the stage of elaboration of the material, discussion, demonstration and evaluation of activities, with the number of participants who took part in this activity as many as 10 people. From the results of this training activity, Setalik Village's superior product can be created, namely fern chips. This activity not only provided knowledge about fern chips, but also related to the legality of products in the form of P-IRT. The hope of the people of Setalik Village is that they want to know more about innovative products, especially in the food sector, so that people can better utilize local food ingredients in the local community. Based on the results of the training on making fern chips for PKK/Posyandu cadres in Setalik Village, it can be concluded that the participants had good enthusiasm in this activity. It is hoped that this activity can increase the knowledge and ability of rural communities in developing superior food products.